Direction for optimization of the training process in junior hockey - Kygaevskiy, S.A. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2014)
Purpose: to consider the possible directions of optimization of training activity in youth hockey and offer practical advice. Material : study analyzed data from the literature and the latest achievements in the practice of training the player’s domestic and foreign authors on training in youth sports. Results : innovative approaches are considered in the initial stages of training sports perfection, as well as various areas of optimization of the training process in the initial stages of hockey and preliminary basic training. The examples of the training process in the North American and European hockey schools. The questions concerning the construction and orientation of training process at the initial stages and pre- basic training. Conclusions : highlighted promising areas for optimization of the training process of young hockey players in the initial stages of sports perfection.